Prevalence and factors associated with pelvic floor dysfunction in university women: a cross-sectional study - Iamundo, Luana Fávaro [UNESP]; de Aquino Nava, Guilherme Thomaz [UNESP]; Rocha, Paulo Roberto; Prudencio, Caroline Baldini [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP] (FapUNIFESP (SciELO), 2022)
Introduction: Urinary incontinence (UI), fecal incontinence (FI), and genito-pelvic pain or penetration disorder (GPPPD) are considered pelvic floor dysfunction (PFD), and are mainly characterized by poor functionality of the pelvic floor muscles. Despite the relevance of these dysfunctions in women's lives, the demand for care is low. Objective: To analyze the prevalence of PFD, in university women, and factors associated with PFD. Methods: This is a cross-sectional study conducted at São Paulo State University, Marília, SP, Brazil, with undergraduate and/ or postgraduate women aged over 18 years. An online questionnaire containing 40 open and multiple-choice questions about PFD was developed by the authors and a Google form was disclosed via social media (Facebook, Instagram) to the participants. The questionnaire was applied between April and July 2020. Results: A sample of 707 participants was included. The average age was 22.5 ± 21.0 years old. The most prevalent PFD was GPPPD, reported by 30.7% of women, followed by UI (16.8%) and FI (3.2%). PFD was significant less reported in the Midwest region compared to other regions (p = 0.015) and significantly more prevalent in women who attended public university (p = 0.038), in women with UI, FI, and GPPPD. The association-test showed that attending public university showed association to UI (p < 0.001), FI (p = 0.008) and GPPPD (p = 0.006). In addition, parity showed association with GPPD (p = 0.032) and to attend health courses with UI (p = 0.002). Conclusion: PFD is prevalent among university women and GPPPD was the most recurrent, followed by UI and FI. GPPPD was associated with parity and attending a public university. UI was associated with attending public university and health courses. FI was associated with attending a public university
Prevalência e fatores associados à disfunção do assoalho pélvico em mulheres universitárias: um estudo transversal
Keywords: Pelvic floor disorders; Physiological sexual dysfunction; University; Urinary incontinence